DESING AND PROPERTIES OF SPLIT MASTIC ASPHALT MODIFY WITH BAGASSE ASH - Lhwaint, Abdallh; Setyawan, Ary; Astuti, Winny (Jurnal Teknik Sipil, 2015)
AbstractGo green campaign is one of ways to save the earth from garbage. Thiscampaign not only suggestsrecycling and reducing but also reusing the garbage. In line with the go green campaign, the aim of this study is to achieve the viability of using Bagasse Ash (BA) as additive material in hot mix Split Mastic Asphalt (SMA) with certain comparison which is expected to improve the quality of SMA. This research was conducted by using experiment research design in comparison among the three types of (without BA and with BA)properties of the hot SMA toward the Marshall properties (stability, flow, Marshall Quotient (MQ), Void In Total Mix (VITM), Void Filled Without Asphalt (VFWA),and Air Void to get Optimum Bitumen Content ,Indirect Tensile Strength (ITS) at different temperature (20oC,40oC,60oC) and Unconfined compressive at same temperature room at 27oC but different percentage of BA (3%,4% ,5%). The results of this research are as follows: 1) the properties of the hot mix SMA toward the Marshall properties are: The stability value of SMA with BA is higher than SMA withoutBA by 3%; The flow value of SMA with BA is lower than SMA without BA by 5.5%; The Marshall Quotient value of SMA with BA is higher than SMA without BA by 5%; TheAir void value of SMA withBA is lower than SMA without BA by 3%; The VFWA value of SMA with Bagasse Ash is higher than SMA without BA by 75.87%; The Air Void value of SMA with BA is lower than SMA without BA by 2%.In terms of ITS value, the value of ITS is high when BA is combined with low temperature; but when the temperature is increased, the value of ITS decreases. Moreover, in terms of UCS, the value of UCS of BA mixture is higher than SMA and higher than normal mixture at normal temperature. The recommendation of this research is that a certain percentage of air voids is necessary in all dense-graded mixes to prevent the pavement from flushing, shoving, and rutting. Air voids may be increased or decreased by lowering or raising the binder content. They may also be increased or decreased by controlling the amount of material passing the No. 200 sieve in the HMA. The more fines added to the HMA generally the lower the air voids. The air voids may be changed by varying the aggregate gradation in the HMA.Keywords: Bagasse Ash, Split Mastic Asphalt, ITS, UCS